The Assessment Of Implementation Four Primary Strategies In Over Coming Of TBC At Public Health Centre Of Sokaraja II - Aris Fitriyani; Siti Mulidah; Widjijati Widjijati (Jurnal Riset Kesehatan, 2012)
This research was to assess the implementation four primary strategies in over coming of TBC. The research was a qualitative research with phenomenology approach. The number of informant were 5. Analisys tecnic of the research used interactive analisys with trianggulation of informant. The result of the research showed four primary strategies for over coming of TBC which were 1) information promotion , 2) Case elimination strategy, 3) Rolle strategy, 4) Assistant strategy .